(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the organizational and content features of the international cultural and educational event "The Language of Patterns - the Echo of a Common Heritage", held for the first time in April 2026 at the State Museum of the History of Applied Arts and Crafts of Uzbekistan in Tashkent, as well as its scientific and practical significance. This event included a scientific and practical conference "Culture Coded in Decorations", an exhibition of unique handicraft products, and more than 12 master classes in national pattern art with the participation of craftsmen from Uzbekistan and Azerbaijan. A total of more than 80 participants took part in the event, and more than 20 master craftsmen from both countries demonstrated their creative works. The article also examines the dynamics of the development of Uzbek-Azerbaijani cultural cooperation in recent years, the results of the "Heritage in Stitches" exhibition held in Baku in 2024, and the continuity between the event in 2026.